Invariant tori of linear countable systems of discrete equations given on an infinite-dimensional torus - Samoilenko, A. M.; Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We study the problem of existence and uniqueness of invariant toroidal manifolds of countable systems of linear equations given on an infinite-dimensional torus.